The Relationship of Egg Weight with DOC Weight and DOC Weight with Body Weight of First Generation of Sentul Chicken (G1) - Muhammad Abdu; Gushairiyanto Gushairiyanto; Depison Depison (JURNAL ILMIAH PETERNAKAN TERPADU, 2021)
This study aims to determine the relationship between egg weight and DOC weight and DOC weight with body weight of Sentul GI chickens at 1, 2, 3, and 4 months of age. The materials used were 78 males and 96 females of Sentul G1 chickens from the hatching of 315 G0 eggs. The research method is the experimental method. The variables of this study included: egg weight, body weight and body weight gain at DOC-4 months of age. Data analysis used t-test and correlation regression analysis. Egg weight had no significant effect (P≥0.05) on the sex of Sentul chicken DOC. The average body weight of male Sentul chickens was significantly (P <0.05) higher than that of female Sentul chickens. Egg weight had a significant effect (P<0.05) on DOC weight with a correlation value of 0.915 and 0.892. DOC weight had a significant effect (P<0.05) on body weight at the age of 1, 2, 3, and 4 months with the correlation values of Sentul roosters sequentially 0.892, 0.794, 0.757, 0.539 and Sentul hens correlation values sequentially 0.993, 0.859, 0.735 , 0.527. Conclusion: 1) Average egg weight, body weight, and body weight gain of male Sentul chickens were better than female Sentul chickens G1. 2) The relationship between egg weight and DOC weight and DOC weight at 1, 2, 3 and 4 months of age was positive.